Coastal wetlands : an integrated ecosystem approach - Perillo, G. M. E. (Elsevier, 2009)
Coastal wetlands are under a great deal of pressure from the dual forces of rising sea level and the intervention of human populations both along the estuary and in the river catchment. Direct impacts include the destruction or degradation of wetlands from land reclamation and infrastructures. Indirect impacts derive from the discharge of pollutants, changes in river flows and sediment supplies, land clearing, and dam operations. As sea level rises, coastal wetlands in most areas of the world migrate landward to occupy former uplands. The competition of these lands from human development is intensifying, making the landward migration impossible in many cases. This book provides an understanding of the functioning of coastal ecosystems and the ecological services that they provide, and suggestions for their management. In this book a CD is included containing color figures of wetlands and estuaries in different parts of the world. This title includes a CD containing color figures of wetlands and estuaries in different parts of the world.
Keywords: Estuarine restoration.; Coastal zone management.; Wetland ecology.; Coasts.; elektronické knihy; electronic books